OmpA and OmpC are critical host factors for bacteriophage Sf6 entry in Shigella. Issue 1 (6th March 2014) - Parent, Kristin N.; Erb, Marcella L.; Cardone, Giovanni; Nguyen, Katrina; Gilcrease, Eddie B.; Porcek, Natalia B.; Pogliano, Joe; Baker, Timothy S.; Casjens, Sherwood R.
Summary Despite being essential for successful infection, the molecular cues involved in host recognition and genome transfer of viruses are not completely understood. Bacterial outer membrane proteins A and C co‐purify in lipid vesicles with bacteriophage Sf6, implicating both outer membrane proteins as potential host receptors. We determined that outer membrane proteins A and C mediate Sf6 infection by dramatically increasing its rate and efficiency. We performed a combination of in vivo studies with three omp null mutants of Shigella flexneri, including classic phage plaque assays and time‐lapse fluorescence microscopy to monitor genome ejection at the single virion level. Cryo‐electron tomography of phage 'infecting' outer membrane vesicles shows the tail needle contacting and indenting the outer membrane. Lastly, in vitro ejection studies reveal that lipopolysaccharide and outer membrane proteins are both required for Sf6 genome release. We conclude that Sf6 phage entry utilizes either outer membrane proteins A or C, with outer membrane protein A being the preferred receptor.